2010
DOI: 10.1039/c0dt00628a
|View full text |Cite
|
Sign up to set email alerts
|

Redetermination of the X-ray structure of nitroxylcobalamin: base-on nitroxylcobalamin exhibits a remarkably long Co–N(dimethylbenzimidazole) bond distance

Abstract: The X-ray structures of three new crystals of nitroxylcobalamin (NOCbl) have been determined. Unlike our earlier reported structure in which NOCbl was partially oxidized , the O atom of the nitroxyl ligand is located in a single position with a N=O bond distance of 1.12-1.14 Å, consistent with a double bond. The Co-N-O angle is in the 118.9-120.3 Å range. The α-axial Co-N(dimethylbenzimidazole) (Co-NB3) bond distance is a remarkable 2.32-2.35 Å in length, ~0.1 Å longer than that reported for all other cobalami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 35 publications
4
34
0
Order By: Relevance
“…Very recently, Brasch et al have shown that extension of this correlation to a larger number of cobalamins having distances with e.s.d. 's up to 0.01 Å, gave an R 2 value of 0.84 [39,40,43]. However, when the correlation is limited to Co\NB3 distances with e.s.d.…”
Section: Co-c (å)mentioning
confidence: 90%
See 1 more Smart Citation
“…Very recently, Brasch et al have shown that extension of this correlation to a larger number of cobalamins having distances with e.s.d. 's up to 0.01 Å, gave an R 2 value of 0.84 [39,40,43]. However, when the correlation is limited to Co\NB3 distances with e.s.d.…”
Section: Co-c (å)mentioning
confidence: 90%
“…2. The distance increases from 1.925(2) Å, when X is the very weak σ-donor H 2 O, to 2.351(2) Å, when X is the strong σ-donor NO: the latter is a significantly stronger trans influencing ligand than even an alkyl group [39,40]. In contrast to NOCbl, nitrosylcobaloxime is pentacoordinate and represents, to our knowledge, the only example so far known of a crystallographically characterized pentacoordinate Co(III) dioximate [41].…”
Section: Trans Influencementioning
confidence: 97%
“…Hence K cyanide = K obs K azide , where K obs is the observed equilibrium constant for binding of CN À in the presence of excess N 3 À . By analogy with [ACCbs] + and [ACSYCbs] + [1,27], both [AC(10-NO 2 )Cbs] + and [AC(10-NH 2 )Cbs] + exist in solution as an equilibrium of two diastereomers, viz., a-cyano, b-aqua and a-aqua, b-cyano. The two diastereomers should have similar, but not identical, equilibrium constants.…”
Section: àmentioning
confidence: 97%
“…Di-aqua (or aquahydroxo) species due to CN À ligand exchange reaction may be present since aquacyano cobesters interchange between the a-CN À , b-H 2 O and b-CN À , a-H 2 O isomers; this presumably occurs through intermediate formation of a bimolecular species with CN À acting as a bridging ligand, leading to the dicyano and diaqua (or aquahydroxo) species [1,17,27]. The observations of pK a s at around 8.5 and between 3 and 5.5, and the relatively small absorbance changes associated with these is evidence for the existence of di-aqua and aquahydroxo species in solution (see above, and Fig.…”
Section: Kineticsmentioning
confidence: 99%
See 1 more Smart Citation